THE INFLUENCE OF INDEPENDENCE AND LEARNING ENVIRONMENT ON INTEREST IN STUDYING STUDENTS OF FINANCIAL ACCOUNTING AND INSTITUTIONS - Indi Maghfira; Masnawaty S; Siti Hajerah Hasyim (LPPM Universitas Labuhanbatu, 2023)
Abstract This research aims to determine: 1) the influence of independence and the learning environment simultaneously on the learning interest of students majoring in financial and institutional accounting at SMK Negeri 2 East Luwu, 2) the influence of independence and the learning environment partially on the interest in learning of students majoring in financial accounting and institutions in East Luwu State Vocational School 2, and 3) the most dominant variable influencing the learning interest of students majoring in financial and institutional accounting at East Luwu State Vocational School 2. The variables in this research are learning independence as the first independent variable (X1), learning environment as the second independent variable (X2) and learning interest as the dependent variable (Y). The population in this study was 117 students from the Department of Financial Accounting and East Luwu State Vocational School 2 for the 2022/2023 academic year. The sampling technique used was simple random sampling with a sample of 54 students chosen randomly without paying attention to the strata in the population. . The data collection techniques used are questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing, and hypothesis testing. The instrument test consists of a validity test and a reliability test. Hypothesis testing consists of normality test, multiple linear regression, simultaneous test (F test), multiple coefficient of determination (R2), partial test (t test) and partial coefficient of determination (r2). The results of this study indicate that learning independence and the learning environment simultaneously have a significant effect on interest in learning with a significance level of <0.05. Meanwhile, the coefficient of determination (R^2) is 0.457 (45.7%). This means that the influence of student learning independence and the learning environment on learning interest is 45.7%, while the remaining 54.3% is influenced by other factors that were not researched. Apart from that, learning independence partially has a significant effect on interest in learning with a significance level of <0.05 and the learning environment partially has a significant effect on interest in learning with a significance level of <0.05. And independent learning has a dominant influence on interest in learning with a coefficient of determination of 0.394 (39.4%).. Keywords: Learning Independence, Learning Environment, and Interest in Learning.